Peran Mahasiswa Dalam Pendampingan Legalitas Lembaga Pendidikan Keagamaan: Yayasan Al-Hidayatut Tarbiyatul Islamiyah - Nur Muhammad Saifurrijal; Afnana Lailatul Inayah; Jamalulel; Muhammad Ihsan Gifari; Lailatul Magfiroh (Inisiatif : Jurnal Dedikasi Pengabdian Masyarakat, 2025)
This community service research discusses the role of students in assisting religious educational institutions with legal matters, using the Al-Hidayatut Tarbiyatul Islamiyah Foundation as a case study. Legality is a fundamental aspect for a foundation to have legal power, obtain official recognition, and open access to government support and external partners. However, many foundations still face obstacles in terms of administration, understanding regulations, and limited resources. Students act as assistants who play a role in disseminating information about regulations, helping to prepare legal documents, and assisting in the process of applying for legality to the relevant agencies. This study uses a descriptive qualitative method through observation, interviews, and documentation. The results show that student assistance contributes significantly to facilitating the foundation's legalization process, increasing the administrators' awareness of the importance of administrative governance, and strengthening the position of the Al-Hidayatut Tarbiyatul Islamiyah Foundation as a legally recognized religious educational institution. Thus, the synergy between students and the community through legal assistance can have a positive impact on the sustainability and development of religious educational institutions. Keywords : Students; Legal Assistance; Religious Education.